RELATIONAL AGGRESSION AMONG MALAY ADOLESCENTS IN SELANGOR: EXAMINING EMOTION REGULATION AND PEER INFLUENCE - Zaki, Azimah Ahmad; Ismail, Nellie; Arshat, Zarinah (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
Relational aggression, a behaviour intended to harm social relationships, is often overlooked compared to other forms of aggression, though it has significant effect on mental health and social development. Although concerns about bullying and aggression in schools are increasing, research focusing specifically on relational aggression in Malaysia remains scarce. Emotion regulation and peer influence have been identified as important correlates of relational aggression, yet little is known about how these factors operate across genders. This study examined the relationship between emotion regulation, peer influence, and relational aggression among Malay adolescents, and assessed whether the independent variables varied by gender. Participants were 403 students from public secondary schools in Selangor. Missing data were addressed using multiple imputation in R, with both parametric and non‑parametric methods applied to ensure robust results. Results indicated that peer influence was positively associated with relational aggression across methods, whereas emotion regulation strategies were not significantly related. Boys reported higher levels of relational aggression and peer influence than girls, but no gender differences were found in emotion regulation. The findings highlight the importance of peer based and gender sensitive interventions for reducing relational aggression and promoting healthier adolescent development. By situating relational aggression within the Malaysian context and incorporating gender perspectives, this study contributes to a more nuanced understanding of adolescent social development and its risk factors. These findings suggest that peer‑focused, gender‑sensitive interventions are critical for reducing relational aggression and promoting healthier adolescent development. The study contributes to the growing body of Malaysian research by integrating gender perspectives into the analysis risk-factors influencing relational aggression.